Is cholecystectomy really an indication for concomitant splenectomy in mild hereditary spherocytosis?. Issue 8 (7th June 2010) - Alizai, Naved K; Richards, E Michael; Stringer, Mark D
Abstract : Background/aim: The British Committee for Standards in Haematology currently recommends concomitant splenectomy in children with mild hereditary spherocytosis (HS) undergoing cholecystectomy for symptomatic gallstones. However, splenectomy is associated with a risk of life-threatening infection, particularly in young children. The aim of this study was to audit the outcome of the practice of uncoupling splenectomy and cholecystectomy in such patients. Methods: Children referred with symptomatic gallstones complicating HS between April 1999 and April 2009 were prospectively identified and reviewed retrospectively. During this period, the policy was to undertake concomitant splenectomy only if indicated for haematological reasons and not simply because of planned cholecystectomy. Results: A total of 16 patients (mean age 10.4, range 3.7 to 16 years, 11 women) with HS and symptomatic gallstones underwent cholecystectomy. Three patients subsequently required a splenectomy for haematological reasons 0.8–2.5 years after cholecystectomy; all three splenectomies were performed laparoscopically. There were no postoperative complications in the 16 patients; postoperative hospital stay was 1–3 days after either cholecystectomy or splenectomy. The 13 children with a retained spleen remain under regular review by a haematologist (median follow-up 4.6, range 0.5 to 10.6 years) and are well and transfusion independent. Conclusions: The advice to perform a concomitant splenectomy in children with mild HS undergoing cholecystectomy for symptomatic gallstones needs revisiting. In the era of minimal access surgery, the need for splenectomy in such children should be judged on its own merits.